2017
DOI: 10.13057/nusbiosci/n090409
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Antibacterial activity of certain Saudi Arabian medicinal plants used in folk medicine against different groups of bacteria

Abstract: Al-Ghanayem AA, Al Sobeai SM, Alhussaini MS, Joseph B, Saadabi AM. 2017. Antibacterial activity of certain Saudi Arabian medicinal plants used in folk medicine against different groups of bacteria. Nusantara Bioscience 9: 392-395. Medicinal plants from Saudi Arabia has been used in folk medicine for treatment of many diseases. The present research is on medicinal plants, which are locally available such as Acacia ehrenbergiana (Arabic: Salam) (Fabaceae), Calotropis procera (Arabic: Ausher) (Apocynaceae), Halox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Plant active ingredients can be good candidates for the biological activity of plants besides nanoparticles (NPs) formulation since are known as reducing and capping agents. The importance of L. scindicus as a medicinal plant was earlier studied and the antifungal and antibacterial abilities of P. turgidum were reported 5 , 6 , however, no valid report about their anticancer ability and their ability in NPs fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Plant active ingredients can be good candidates for the biological activity of plants besides nanoparticles (NPs) formulation since are known as reducing and capping agents. The importance of L. scindicus as a medicinal plant was earlier studied and the antifungal and antibacterial abilities of P. turgidum were reported 5 , 6 , however, no valid report about their anticancer ability and their ability in NPs fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…There are earlier studies establishing a wide range of antibacterial activities for Acacia ehrenbergiana [ 4 , 12 , 13 , 22 ]. On testing the antibacterial activities of Acacia ehrenbergiana, a significant effect was found for the acetone and ethanol extracts on Gram-negative E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported that Gram-positive bacteria are more susceptible to plant extracts (Al-Ghanayem et al 2017;Boussaada et al 2008;Semeniuc et al 2017). In contrast, we observed that the hexane extract of L. aduncum had stronger antimicrobial activity against Gram-negative bacteria than Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%